An Analysis of Heidegger’s Critique of Metaphysics’ Approach to the Nothing from a Muslim Philosopher's perspectives - Hassanpoor, Alireza; Nazari, Javad (Revista de Filosofía, 2023)
Heidegger’s most significant critique of metaphysics is that the history of metaphysics is the history of the forgetting of being. However, he also criticizes metaphysics for forgetting the nothing. Metaphysics fails to adequately address both being and nothingness, neglecting the nothing and treating it as a conceptual abstraction without objective reference. Metaphysics reduces discussions of the nothing to mere figurative expressions. However, by drawing on the approach of a contemporary Muslim philosopher who examines the the problem of the nothing in particular and the fact-itself and reality in general, and the division of being into general, real, and specific, we can respond to Heidegger’s critique within the framework of metaphysics. According to this perspective, the nothing, like being, is an integral part of reality in a general and real sense. The nothing, with its nothingness, manifests itself in the external world without being reduced to the being. Thus, Heidegger’s statement that “nothing nihilates (or noths) itself” finds metaphysical justification.